Regulatory T cells and IL10 suppress pulmonary host defense during early-life exposure to radical containing combustion derived ultrafine particulate matter. Issue 1 (December 2017) - Jaligama, Sridhar; Saravia, Jordy; You, Dahui; Yadav, Nikki; Lee, Greg; Shrestha, Bishwas; Cormier, Stephania
Abstract Background Exposure to elevated levels of particulate matter (PM) is associated with increased risk of morbidity and mortality due to respiratory tract viral infections in infants. Recent identification of environmentally persistent free radicals (EPFRs) in the PM from a variety of combustion sources suggests its role in the enhancement of disease severity of lower respiratory tract infections (LRTI). Our previous studies demonstrated that acute exposure to EPFRs induces pulmonary immunosuppression allowing for enhanced influenza disease severity. Here, we determine the mechanism of EPFR-induced immunosuppression and its impact on the immune response towards influenza infection. Methods Neonatal mice (3 days old) were acutely exposed to DCB (combustion derived PM with chemisorbed EPFR) for seven consecutive days. Four days post-exposure (dpe), mice were infected with influenza virus. Pulmonary T cell phenotypes including regulatory T cells (Tregs) were analyzed by flow cytometry. The role of IL10 in EPFR-induced exacerbation of influenza disease severity was determined by administering recombinant IL10 (rIL10) to wild type mice or by using IL10 deficient (IL10−/− ) neonatal mice. Mice were assessed for morbidity by measuring percent weight change and pulmonary viral load. Results Neonatal mice exposed to EPFRs had a significant increase in pulmonary Tregs and the immunosuppressive cytokine IL10 following influenza infection, which coincided with decreased protective T cell responses to influenza infection at 6 dpi. Depletion of Tregs in EPFR-exposed neonatal mice resulted in increased protective, adaptive T cell responses, whereas adoptive transfer of Tregs from EPFR-exposed neonates to air-exposed neonatal mice suppressed adaptive T cell responses towards influenza infection. Further, treatment with rIL10 could recapitulate EPFR-induced exacerbation of morbidity and pulmonary viral load compared to air exposed and influenza infected mice, whereas, EPFR-exposed IL10−/− neonates exhibited significant reductions in morbidity, pulmonary viral load and adaptive T cell responses following influenza infection. Conclusions Neonatal exposure to EPFRs induced Tregs and IL10 resulting in suppressed adaptive T cell responses and enhanced influenza disease severity in neonatal mice. Depletion of Tregs increased adaptive T cell responses and deficiency of IL10 reduced morbidity and conferred enhanced protection against influenza virus.